Degradation of Diallyl Phthalate (DAP) by Fenton Oxidation: Mechanistic and Kinetic Studies - Sondos Dbira (16488920) (2018)
In this work, the degradation and mineralization of Diallyl Phthalate (DAP) in water by Fenton oxidation was investigated. The effects of different experimental parameters including the initial pH, the hydrogen peroxide (H2O2) dose, the catalyst (Fe2+) dose, the iron source, and the DAP concentration on the rate and the yield of DAP degradation by Fenton oxidation were evaluated. DAP and its intermediates were quantified by high performance liquid chromatography (HPLC) analysis and the measurement of total organic carbon (TOC) during Fenton oxidation. The results obtained confirmed that hydroxyl radicals (HO•) generated from Fenton’s reaction were capable of completely eliminating DAP from water. Fenton oxidation of 100 mg/L DAP aqueous solution at pH = 3.2 required 1000 mg/L H2O2 and 50 mg/L Fe2+. Under these conditions, more than TOC removal exceeded 95% after 300 min Fenton oxidation. The competition kinetics method was used to determine an absolute rate constant of 7.26.109 M−1 s−1 for the reaction between DAP and HO• radicals. HPLC analysis showed that phthalic acid, 1,2-dihydroxybenzene, 1,2,4-trihydroxybenzene, maleic acid, formic acid and oxalic acid were the main intermediates formed during DAP degradation. Accordingly, a simple DAP degradation mechanism by the Fenton reaction was proposed. These promising results proved the potential of Fenton oxidation as a cost-effective method for the decontamination of wastewaters containing phthalates. Other Information Published in: Applied Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/app9010023